The perception of empathy. - Sanahuges, Carme; Curell, Hortènsia (Círculo de Lingüística Aplicada a la Comunicación, 2022)
In the present article, we aim to identify, analyse and correlate the variables underlying the perception of empathy based on the evaluations made by the role play participants of their own interactions. The subjects, whose L1 was either Catalan or English, held a conversation dealing with a trouble that aimed to elicit an empathic response. Each participant assessed the effects that those dyad dialogues had on them by completing a questionnaire in which different elements were included depending on whether they were the empathy receiver or the empath provider. Although partially grounded on conversational aspects, the analysis of the items favours a more psychology-oriented approach since they involve subjective cognitive and emotional factors. The results show the positive effects of empathy-related verbal strategies on the empathy receiver and the central importance of understanding and appraisal in the construction of empathy. The results also point to the mutual influence of interactional participants on each other. By identifying the significant correlations established between the variables considered, we hope to contribute to the understanding of the impact of empathic conversations on the participants.